An overview of the HIBISCUS campaign - Pommereau, J. -P.; Garnier, A.; Held, Gerhard [UNESP]; Gomes, A. M. [UNESP]; Goutail, F.; Durry, G.; Borchi, F.; Hauchecorne, A.; Montoux, N.; Cocquerez, P.; Letrenne, G.; Vial, F.; et al. (Copernicus Gesellschaft Mbh, 2011)
The EU HIBISCUS project consisted of a series of field campaigns during the intense convective summers in 2001, 2003 and 2004 in the State of São Paulo in Brazil. Its objective was to investigate the impact of deep convection on the Tropical Tropopause Layer (TTL) and the lower stratosphere by providing a new set of observational data on meteorology, tracers of horizontal and vertical transport, water vapour, clouds, and chemistry in the tropical Upper Troposphere/Lower Stratosphere (UT/LS). This was achieved using short duration research balloons to study local phenomena associated with convection over land, and long-duration balloons circumnavigating the globe to study the contrast between land and oceans.Analyses of observations of short-lived tracers, ozone and ice particles show strong episodic local updraughts of cold air across the lapse rate tropopause up to 18 or 19 km (420-440 K) in the lower stratosphere by overshooting towers. The long duration balloon and satellite measurements reveal a contrast between the composition of the lower stratosphere over land and oceanic areas, suggesting significant global impact of such events. The overshoots are shown to be well captured by non-hydrostatic meso-scale Cloud Resolving Models indicating vertical velocities of 50-60 m s(-1) at the top of the Neutral Buoyancy Level (NBL) at around 14 km, but, in contrast, are poorly represented by global Chemistry-Transport Models (CTM) forced by Numerical Weather Forecast Models (NWP) underestimating the overshooting process. Finally, the data collected by the HIBISCUS balloons have allowed a thorough evaluation of temperature NWP analyses and reanalyses, as well as satellite ozone, nitrogen oxide, water vapour and bromine oxide measurements in the tropics.